DNA sequence of the region in the genome of herpes simplex virus type 1 containing the exonuclease gene and neighbouring genes. - McGeoch, D J (1986)
We report the sequence of a 7800 base pair region of herpes simplex virus type 1 DNA, representing approximately 0.16 to 0.20 map units in the genome. This contains sequences transcribed into a leftward oriented set of five 3' coterminal mRNAs, together with two rightward transcribed flanking genes. One of the leftward genes encodes the virus's alkaline exonuclease, but the other gene products are uncharacterized. The amino acid sequence of one encoded protein suggested that it is a membrane embedded species. The DNA sequence is densely utilised, with two predicted out-of-frame overlaps of coding sequences, and probably six occurrences of promoter elements within coding sequences. Homologues of five of the genes were found for the distantly related Epstein-Barr virus, with a similar overall relative arrangement.